2011
DOI: 10.1111/j.1440-1819.2011.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide‐related events among child and adolescent patients during short‐term antidepressant therapy

Abstract: Aims: Antidepressants have been of limited use for adolescent subjects with depression because of druginduced suicide-related events (SRE). Therefore, we investigated actual suicidality and its risk factors during antidepressant therapy among child and adolescent patients in clinical settings. Methods:The risks of SRE, consisting of suicidal ideation, self-mutilation and suicide attempt, were prospectively monitored among 70 child and adolescent patients (15.4 Ϯ 2.8 years) during the first 3 months of antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(70 reference statements)
3
17
0
Order By: Relevance
“…Beyond loss of physical energy and sexual activity, loss of interest and loss of pleasure are incrementally predictive of greater suicidal ideation (Winer et al, 2014a). Even research examining the effect of antidepressants found that pre-treatment anhedonia predicted risk of suicide-related events at treatment termination (Kuba et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Beyond loss of physical energy and sexual activity, loss of interest and loss of pleasure are incrementally predictive of greater suicidal ideation (Winer et al, 2014a). Even research examining the effect of antidepressants found that pre-treatment anhedonia predicted risk of suicide-related events at treatment termination (Kuba et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…One study found significant levels of anhedonia in 37% of people with depression and 45% of people with schizophrenia (Pelizza & Ferrari, 2009). Other conditions linked to anhedonia include substance dependence (Martinotti et al, 2011; Rose et al, 2012), anxiety (Dinovo & Vasey, 2011), suicide related events (Kuba et al, 2011), post-traumatic stress disorder (Pittman, Goldsmith, Lemmer, Kilmer, & Baker, 2012; Wechsler-Zimring & Kearney, 2011), autism (Chevallier, Grezes, Molesworth, Berthoz, & Happe, 2012), Parkinson’s disease (Fujiwara et al, 2011; Miura et al, 2012), stroke (Sibon, Lassalle-Lagadec, Renou, & Swendsen, 2012), and some chronic medical conditions (de Cock, Emons, Nefs, Pop, & Pouwer, 2011; Nefs, Pouwer, Pop, & Denollet, 2012; Pelle et al, 2011; P. J. Tully & Baker, 2012).…”
Section: Concept Analysis Resultsmentioning
confidence: 99%
“…Along similar lines, one other study found that pre-treatment patient characteristics largely accounted for increased suicidality (Kuba et al 2011), while others have stated that the studies which formed the basis of the FDA regulatory decision were limited due to the exclusion of suicidal adolescents in clinical trials (Antonuccio 2008, Jureidini and McHenry 2009)…”
Section: Introductionmentioning
confidence: 88%